Improving intellectual capital management mechanisms in the context of dynamic digital transformation of the global market environment - Sydoruk, Iryna; Voronkova, Alla; Imanova, Mehriban (Актуальні питання економічних наук, 2026)
The study’s relevance stems from the strengthening of the role of intellectual capital as a key resource for enterprise competitiveness in the context of digital transformation, military challenges, the migration of specialists and rapid technological changes. In such conditions, traditional approaches to intellectual capital management, focused mainly on developing human resources or implementing individual digital tools, do not provide a holistic framework for managing knowledge, competencies, client data and innovations. The purpose of the article is to substantiate the theoretical and methodological principles for improving the mechanism for managing an enterprise’s intellectual capital by forming a digital ecosystem that integrates its components into a single strategic development contour. The methodological basis of the study is the systemic, comparative, structural-logical and generalizing approaches. The paper analyzes scientific views on the essence, structure and mechanisms of intellectual capital management and compares models of its formation in Ukraine and worldwide. Results. The need to transition from fragmented management of individual components of intellectual capital to a holistic mechanism is substantiated. The author proposes a structural and logical scheme for the digital ecosystem of intellectual capital management in an enterprise and identifies directions for improving mechanisms for managing its components within a single strategic contour. Human capital is considered in terms of its traditional and resilient components, which significantly expand the basic ideas about its role and influence in the formation and development of intellectual capital. The traditional interpretation of client capital is translated into the plane of brand reputation formation and building personalized interaction, and technological innovations and organizational capital are defined as the basis for integrating all elements of intellectual capital into a single mechanism. The practical significance of the work lies in the possibility of using the proposed digital ecosystem to improve the mechanisms for managing intellectual capital of enterprises by integrating human, client and organizational capital, technological innovations and brand reputation into a single contour of strategic development using digital tools, the capabilities of professional communities and personalized communication of social platforms. Conclusions. The results obtained provide grounds to conclude that the digital ecosystem can be regarded as an improved mechanism for intellectual capital management, ensuring the coordinated interaction of its components and enhancing enterprises’ adaptability to digital transformation and external environmental instability.